Analysis of Police Investigation Reforms in Khyber Pakhtunkhwa Police Act 2017 (Journal of Social Sciences Review, 2023)
The process of Police Investigation Reforms in Pakistan is a part of the accountability of the police to ensure transparency and the rule of law. The police have been mandated a permanent disciplinary and executive task of investigating offences of different natures, conducting inquiries in different cases to be submitted to the superior courts and giving recommendations to the lower courts for improving the ratio of conviction. The present study focuses on the analysis of the investigation procedure, considering the international standards of the investigation process. With the help of this study, an attempt has been made to highlight the legal and procedural investigation process.
Keywords: Khyber Pakhtunkhwa; Police; Investigation; Reforms